Cardio-oncology: challenges in modern medicine - Rassaf, Tienush (Journal of Thoracic Disease, 2018)
Cardiovascular diseases and cancer and are the main causes for morbidity and mortality in the western world. Progress in the treatment of cancer have greatly improved survival, leading to a dramatic increase of cancer survivors in the next years. Increased survival and age of cancer patients have unmasked the burden of cancer and cancer therapy-associated cardiovascular diseases.